'Nobody works on the platforms for health care or pension': how do platform workers deal with the lack of social protection in a context of structural informality? - Fernández Massi, Mariana (2025)
The rise of platform work, based on atypical forms of labour relationships, challenges those social protection systems in which access to health care, pensions, paid sick-leave, etc. is linked to formal employment. These challenges, faced by all countries, become more critical in those where a large part of the labour force is excluded from formal wage employment, as in Latin American countries. The social protection system in Argentina is a hybrid system. It is organized based on a scheme with a contributory core, but it has non-contributory complements in its most important components. This article aims to understand the positions of platform workers concerning the low coverage provided by their current jobs, articulating a structural analysis with subjective positionings. The analysis is based on 60 in-depth interviews conducted during 2020?2023 in Argentina with workers from three different types of platforms: on-location delivery platforms, online freelancing platforms, and microtask platforms. We identify three main reasons why the concern for social protection increases or decreases: the other jobs with which workers supplement their income, the expectations regarding when social protection will be needed, and the extent of public debate on the rights associated with their specific type of platform work.